EFFECTIVENESS OF TEACHER’S LEARNING STRATEGY FOR CHILDREN’S MOTIVATION, RELIGIOUS AND MORAL VALUE ASPECT - Irma, Irma; Asniwati, Asniwati; Purwanti, Ratna; Cinantya, Celia (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2023)
This examination was roused by the low advancement of children's religious and moral values in group A of TK Kasih Ibu Barito Kuala in sequencing ablution worship movements. The cause is a lack of motivation to follow learning; learning is less interesting and fun. The motivation behind this study is to portray educator exercises, analyze the increase in children's activities, learning motivation, and children's development results in reducing the ablution worship movement. The research method is CAR with a qualitative approach, conducted with 3 meetings with a total of 15 children consisting of 9 boys and 6 girls, which was done with group A children of TK Kasih Ibu Barito Kuala. The results of this study show that teacher activities at meetings I to III get criteria good to very good, the children's activities at meetings I to III get criteria active enough to criteria very active, the learning motivation at meetings I to III get criteria moderately motivated to criteria very motivated, and the results of religious and moral values development meetings I to III get criteria Starting to develop criteria to very well developed criteria.